A new method for extraction of exopolymers from activated sludges - Azeredo, Joana (1998)
The exopolymeric matrix that surrounds the biomass greatly contributes to the efficiency of activated sludge systems. To study the composition of this matrix a preliminary extraction method is required. In this work three extraction methods (vapor, sonication and combined treatment by sonication and Dowex resin) were used and compared with a new method which uses glutaraldehyde. The extraction effectiveness was estimated by measuring the total protein, the total organic carbon in the extracted solutions and by determining the monosaccharide constituents of the extracted polysaccharides. The proposed new method proved to be the most suitable because it extracted a great quantity of organic matter without disrupting the cells.